Dexamathasone Pulse Therapy in Refractory Childhood Seizure Disorders - Ahmed Syed Riaz (Journal of Spine and Neuroscience, 2017)
15 children with variable intractable seizure disorders who were on multiple anti-convulsant medications were treated with pulse monthly doses of parentral dexamethsone varying from 4 – 7 months. EEG and clinical response were assessed periodically as well at the end of the study. 53% of the patients showed clinical response and EEG response. Hypertension was noted in 6, hypokalemia in 3 and hyperglycaemia in 1 patient. The ultimate compliance from the parents for this treatment was seen among 12 patients because of its proven efficacy and parents of seven patients insisted to continue the treatment for long duration.
Keywords: Dexamethasone